Frailty and hearing loss: From association to causation - Liu, Yun; Qian, Peiyi; Guo, Shuli; Liu, Shuangyan; Wang, Dahui; Yang, Lei (Frontiers in Aging Neuroscience, 2022)
Background: Observational studies suggest that frailty is associated with hearing loss (HL) but with inconsistent results. This study aims to examine such association and to assess its causality. Methods: The cross-sectional data from the NHANES. Multivariate logistic regression models were used to assess the association between HL and FI. Genetic variants associated with the FI and HL were obtained from a large genome-wide association study (GWAS) meta-analysis and UK Biobank GWAS. The inverse variance weighting (IVW) method was used to estimate causal effects. Sensitivity analyses were performed to further validate the robustness of results. Results: In this cross-sectional analysis, results support the possibility that frailty may be associated with a higher risk of developing HL, with self-reported (odds ratio (OR) = 2.813; 95% CI, 2.386, 3.317; p < 0.001), speech frequency HL (OR = 1.975; 95% CI, 1.679-2.323; p < 0.001) and high frequency HL (OR= 1.748; 95% CI, 1.459-2.094; p < 0.001). In the adjusted model, frail participants remained at high risk of HL. MR studies showed a bidirectional causal association between genetically predicted FI and risk of HL (FI for exposure: OR = 1.051; 95% CI, 1.020-1.083; p = 0.001; HL for exposure: OR = 1.527; 95% CI, 1.227–1.901; p < 0.001). Conclusion: Our observational study found that inter-individual differences in frailty were associated with the risk of developing HL. Genetic evidence suggests a potential bidirectional causal association between FI and HL. Furthermore, the potential mechanisms of this association require investigation.